Surveying Post-Apartheid Decolonisation of the BMus Curriculum at Four South African Tertiary Music Departments - Struwig, Mieke (Stellenbosch : Stellenbosch University, 2021)
ENGLISH ABSTRACT: This thesis surveys post-apartheid curricular decolonisation at four South African tertiary music departments: Nelson Mandela University, Stellenbosch University, the University of Cape Town (South African College of Music) and the University of KwaZulu-Natal. Data for this survey were obtained through systematic analysis of archival material, focusing on yearbooks and module outlines between 1994 and 2020. This data is supplemented and contextualised by 27 interviews with current and former staff members at the included music departments. The result is a critical curriculum history which, this thesis posits, has the potential to act as a mechanism for change, drawing on Agbedahin and Agbedahin’s (2019) argument for the need for critical university histories. Eurocentrism and coloniality are found to be pervasive in the hidden and explicit curricula of each of the departments, albeit in varying degrees. Chapter one broaches this stubborn tenacity of coloniality and Eurocentrism in the broader context of the university and the discipline of music. The embeddedness of these notions in institutional curricula and the accommodating rapport between coloniality and neoliberalism are demonstrated in chapter two, which provides an account of institutional crisis narratives to understand the institutional environments in which curricular change takes place. Amongst other things, the survey of curricular changes taken from yearbooks and interviews in chapter three points to the sustained presence of hegemonic terminology, the continued positioning of non-traditional musics as optional and marginal and the reduction of curricular change to bureaucratic procedure. Chapter four makes sense of the survey materials of chapter three through a classification of the surveyed changes, followed by a consideration of positions on decolonisation drawn from my interviews. Taken together, this categorisation and the insights from interviews on decolonisation point to an overwhelming reliance on superficial additive strategies for curricular decolonisation that will, at best, leave intact a Eurocentric centre. In closing, the thesis urges researchers, scholars and students to “stay with the trouble” (Haraway, 2016) of decolonisation in their efforts to make “a world just a little better” (Stengers and Despret, 2014:165).